UPAYA PENINGKATAN PENERIMAAN PAJAK PASCA TAX AMNESTY PADA KANWIL DJP BALI - Ida I Dewa A Manik Sastri; Luh Kade Datrini (Behavioral Accounting Journal, 2018)
On July 1, 2016, the Government established Law No. 11 of 2016 concerning Tax Amnesty. This law has been postponed several times, after tough discussions in the House of Representative (Dewan Perwakilan Rakyat – DPR) since 2015. The failure to achieve tax revenues over the past few years has triggered the enactment of this law. The government sees that tax revenues are still low due to a lack of public awareness in reporting taxes, even though the government in the last few years has relied heavily on state revenues from the results of tax revenues. The World Bank notes that Indonesia's tax ratio in 2014 was only 10.84% ​​of Gross Domestic Income, while the average tax ratio of countries in the world was 14.81%. So the level of tax collectibility in Indonesia is still very small, so it is quite heavy in supporting state spending. The purpose of this study was to find out the benefits of tax amnesty as an effort to stimulate national income, to find out the magnitude of the tax amnesty contribution in increasing state revenues, and analyze the influence of several factors in increasing tax revenue after tax amnesty. The implementation of tax amnesty that ended at the end of March 2017 was quite good. The results showed that the number of taxpayers participating in the tax amnesty were 974,058, the amount was still small compared to the potential tax in the country. The amount of state revenue from the Tax amnesty is 107 trillion from 1,104.9 total realized tax revenues in 2016. An important point that must be done immediately after the tax amnesty is the administration update related to data and information management with an integrated IT system with all stakeholders, coordination of tax law enforcement through examination, and institutional transformation.